Protestant ethic: Contributing towards a meaningful workplace - Steenkamp, Petrus L. (HTS teologiese studies, 2013)
Little did Max Weber know that his essay ‘Protestant ethic and the spirit of capitalism’, written in 1905 (which was republished in 1920), would survive the times and still be a source for discussion and interpretation during the 21st century. Today as in previous times, work and the workplace poses its challenges. The common thread through history seems to be attempts to enhance the workplace, to better it, to convert it into a place where people could work with a free spirit. Yet, in spite of all the attempts, one failure after the other has been recorded. In a research program that endeavoured to construe the meaningful workplace, Protestant ethic was identified as one possible contributory towards such an ideal. This article explores the contribution of Protestant ethic as a contributory and sets it within the framework of universal individual values pertaining to work and work-specific values. The article also indicates that the Protestant ethic can indeed contribute towards a meaningful experience whilst performing work-related tasks in workspace. The Protestant work ethic is more than a cultural norm that places a positive moral value on doing a good job. Based on a belief that work has intrinsic value for its own sake, it represents a value system that contributes to the experience of meaningfulness whilst performing work.